Effects of Exogenous Hydrogen Sulfide on Diabetic Metabolic Disorders in db/db Mice Are Associated With Gut Bacterial and Fungal Microbiota - Liu, Jian; Zhao, Wei; Gao, Zi-Wei; Liu, Ning; Zhang, Wei-Hua; Ling, Hong (Frontiers in Cellular and Infection Microbiology, 2022)
The effects of hydrogen sulfide (H2S) on diabetic metabolic disorders are still controversial and the mechanisms underlying these effects remain largely unknown. This study was conducted to investigate the potential relationship between the regulation of diabetic metabolic disorders by exogenous H2S and the gut microbiota in obese db/db mice. The db/db mice were treated with sodium hydrosulfide (NaHS) (80 μmol/kg), or vehicle for 16 weeks, respectively. We measured the serum H2S, obesity parameters, glucose homeostasis and triglyceride. The sequencing of bacterial 16S rRNA gene and fungal internal transcribed spacer (ITS) in the cecal contents of NaHS treated mice was performed to evaluate the gut microbial communities. We found that supplying exogenous H2S for 16 weeks significantly inhibited the increase of serum triglyceride, blood glucose and insulin levels and altered specifically the gut bacterial microbiota structure in db/db mice. The relative abundance of some genera of bacteria was correlated with the H2S or blood glucose level. Indeed, exogenous H2S increased Firmicutes and decreased Bacteroidetes at the phylum level along with changes of abundance of multifarious genera. Among them, Unclassified_Enterobacteriaceae, Prevotella and Lactobacillus decreased and Unclassified_Ruminococcaceae, Oscillospira, Ruminococcus, Sutterella and Desulfovibrio increased. For fungi, exogenous H2S decreased the abundance of Candida and Aspergillus. Here we demonstrated that, in diabetes, microbial dysbiosis may not be just limited to bacteria due to the inter-linked metabolic interactions among bacteria and fungi in the gut. The beneficial effects of exogenous H2S on diabetic metabolic disorders are likely associated with the alterations of specific microbiota.